Marketing Dynamics in the Digital Age: A Literacy Study on the Shift from Traditional Marketing to Social Media - Syaifudin, Syaifudin; Henriawan, Desan; Suzana, Anna; Budianto, Erwin; Oviana, Rena (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
The shift from traditional marketing to social media marketing in the digital age has become a significant phenomenon in the business world. This change is fuelled by technological advancements, especially internet penetration and the increasing use of social media platforms such as Facebook, Instagram, Twitter, and TikTok. Traditional marketing, which relies on one-way communication through mass channels such as television and print, now faces challenges in reaching younger and informed consumers, who prefer more personalised and direct interactions. In contrast, social media offers opportunities for companies to interact directly with consumers, enabling more segmented, personalised and cost-effective marketing. However, social media marketing also comes with challenges, including platform algorithm changes and data privacy concerns. This study aims to explore the shift from traditional marketing to social media marketing, by identifying the challenges and opportunities faced by companies in implementing effective marketing strategies. The study concludes that the integration of both marketing approaches, i.e. traditional and digital, can deliver optimal results for companies, by strengthening relationships with consumers and increasing the effectiveness of marketing campaigns.